Towards a productive model for the Sacha Inchi value chain: A scientometric approach - Flórez-Martínez, Diego Hernando (2023)
The diversification of agricultural and livestock production matrixes has the potential to generate value-added products in industrial and promising crops. Specifically, the countries in the Amazon basin have in the Sacha Inchi (Plukenetia volubilis L.) a species oriented toward market niches such as food, oils, cosmetics, pharmaceuticals, and biofuels, whose exploitation and use are aligned with the bioeconomy and circular economy megatrends. The aim of this publication was to identify and analyze the evolution of scientific and technological research in the Sacha Inchi value chain worldwide, based on a methodological design that combines technological intelligence, the analysis of scientific landscapes and bibliometric indicators and content analysis, to establish a baseline for the identification of key elements for the design of an agro-industrial production model. The methodology includes the integration of surveillance and scientific intelligence methods, scientometrics, and critical analysis of key documents selected through bibliometric indicators and expert judgment. The analysis made it possible to identify the research development lines in Sacha Inchi worldwide, and the reference documents that comprise key elements of the activities from cultivation to processing of the product obtained. The basic investigations identified will contribute to the development of productive models of Sacha Inchi in Colombia, where technical aspects must be adapted or validated in suitable agroecological zones or with productive potential to improve the yield and quality of seed for agroindustry. Medium-term research is required to genetically identify the planting material, to facilitate the selection of materials oriented to the production of fruits with the quality required by the agroindustry.